Strategic Amnesty and Credible Immigration Reform - Chau, Nancy H. (Journal of Labor Economics, 2001)
Why do countries that impose employer sanctions to deter the illegal entry of foreign workers nevertheless grant amnesty to illegal immigrants? In this article, I provide a positive theory of amnesty provision in a model where the constrained optimal immigration reform, involving the joint use of employer sanctions and border interdictions, is time‐inconsistent. In particular, my framework demonstrates that host countries of immigration can enhance the credibility of their immigration reforms by “binding their own hands” and strategically granting a socially excessive amount of amnesty to illegal workers.